1999
DOI: 10.1590/s0034-71081999000300018
|View full text |Cite
|
Sign up to set email alerts
|

Gill infection of Leporinus macrocephalus Garavello & Britski, 1988 (Osteichthyes: Anostomidae) by Henneguya leporinicola n. sp. (Myxozoa: Myxobolidae). Description, histopathology and treatment

Abstract: Piauçus (Leporinus macrocephalus), were raised in 300 m² ponds (density of 10 fish/m²) presenting asphyxia signals and daily mortality of 27 fishes. Specimens with 8-cm total body length, were collected for necropsy. Mucus of body surface and pieces of organs were collected and examined microscopically, in wet mounts, stained or in histological sections. The smears examination showed the presence of several spores in the secondary lamellae of the gill filaments, identified as Henneguya leporinicola n.sp (Myxoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
3
25
0
3
Order By: Relevance
“…In other works, Kalavati and Narasimhamurti (1985), who studied Channa punctatus infected by H. waltairensis, Martins and Souza (1997), who studied the gills of Piaractus mesopotamicus parasitized by Henneguya sp., and Martins et al (1999b), who studied the gills of Leporinus macrocephalus infected by H. leporinocola, hemorrhage and/or inflammatory foci were observed, neither of which was seen here.…”
Section: Discussionmentioning
confidence: 43%
“…In other works, Kalavati and Narasimhamurti (1985), who studied Channa punctatus infected by H. waltairensis, Martins and Souza (1997), who studied the gills of Piaractus mesopotamicus parasitized by Henneguya sp., and Martins et al (1999b), who studied the gills of Leporinus macrocephalus infected by H. leporinocola, hemorrhage and/or inflammatory foci were observed, neither of which was seen here.…”
Section: Discussionmentioning
confidence: 43%
“…Of the 32 Henneguya species recorded so far in the continent, only Henneguya lutzi (Cunha & Fonseca, 1918) cies described in other South American fish, Henneguya santae (Guimarães & Bergamin, 1934) found in Tetragnopterus santae and Henneguya leporinicola (Martins et al, 1999) found in Leporinus macrocephalus share some morphological similarities with H. pellucida, although the first has a smaller caudal process (11.8 µm) and the latter a smaller body spore (7.6 µm) than H. pellucida (body spore length: 11.4 ± 0.3 µm; caudal process length: 24.1 ± 1.5 µm). In Henneguya travassosi (Guimarães & Bergamin, 1933) described in Leporinus copelandi, the spores are approximately equal in size to those of H. pellucida, but are oval in shape, with white plasmodia occurring in the muscles.…”
Section: H Enneguya Pellucida Was Compared With Othermentioning
confidence: 99%
“…C ultivated and wild fishes are infected by numerous myxosporean species of the genus Henneguya Thelohan, 1892, some of which are important pathological agents (Kalavati & Narasimhamurti 1985;Lom & Dyková 1995;Martins et al, 1999). Eiras (2002) listed a total of 146 Henneguya species that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study provide important insights into the myxosporidean infections found in R. quelen, which may cause significant tissue damage (MARTINS et al, 1999;ADRIANO et al, 2005aADRIANO et al, , b, 2006FEIST & LONGSHAW, 2006) or even death (MARTINS et al, 1999;FEIST & LONGSHAW, 2006). A better understanding of this freshwater microparasite fauna will be essential for the prevention and control of diseases in both wild and farmed stocks.…”
Section: Discussionmentioning
confidence: 63%